Where the Shadows Lie : finding the other in the Spatial Depictions of the Underworld in The Book of Enoch, Inferno and Paradise Lost - Schader, Jo-Mari (University of Pretoria, 2013)
Dissertation (MA)--University of Pretoria, 2012.